=3a^3b^3-3a^2b^4-3a^4b^3-3a^3b^4
[b(a^2-ab)-a^2b(a+b)](3ab^2)
1个回答
相关问题
-
由(a+b)(a2-ab+b2)=a3-a2b+ab2+a2b-ab2+b=a3+b3,即(a+b)(a2-ab+b2)
-
A=2a² -3ab+2b²,B=2a²+ab-3b²,则B-A=
-
a^3+a^2b+ab^2+b^3 a+b=3 ab=-2
-
A-B=-1,AB=-2,则(2A-3B-AB)-(A-2B+3AB)=?”
-
当a-b=-1,ab=-2,(2a-3b-ab)-(a-2b+3ab)
-
若a-b=4,ab=1,求(-2ab+2a+3b)-(3ab+2b-2a)-(a+4b+ab)
-
利用公式:(a+b)(a^2-ab+b^2)=a^3+b^3,(a-b)(a^2+ab+b^2)=a^3-b^3.
-
化简:b/(a-b)+b^2/(a^3-2a^2b+ab^3)*(ab+b^2)/(b^2-a^2)
-
计算 (a^2b-ab-a+1)/(ab^2+3ab-b-3)÷(a^2+a_2)/(b^2+b-6)
-
-2ab(3a^2-2ab-4b^2) (2b-a)b-(2a-b)a